The Normative Error Theorist Cannot Avoid Self-Defeat. Issue 1 (2nd January 2020) - Case, Spencer
ABSTRACT: Many philosophers have noted that normative error theorists appear to be committed to saying 'Error theory is true, but I have no reason to believe it', which seems paradoxical. In defence of error theory, some have claimed that the word 'reason' in that statement is ambiguous between 'normative reason' and a purely descriptive sense of 'reason' that the error theorist can accept. I argue, however, that there is no descriptive sense of 'reason' that can prevent the paradox from re-emerging. Moreover, these implications of error theory probably provide good grounds for rejecting the view.